Perilaku berisiko HIV/AIDS pada Remaja SMA di Wilayah Kerja UPTD Puskesmas Harapan Raya Pekanbaru Tahun 2018 - Guspratiwi Syahdinar Abadi; Toha Muhaimin; Lita Lita; Nurlisis Nurlisis; Syamsul Bahri Riva’i; Muhammad Muzakir Fahmi (Sistem Informasi, 2019)
The UPTD Puskesmas the hope of Raya Pekanbaru owns the number of be in the low teens the age of 15-24 the years that came and visited and hiv testing as much as 292 people, have been given counseling as much as 200 people, told there were hiv positive 2 a person, and given chief assessor numbers counseling after the test hiv as much as 207 people. Data on the sexually transmitted infection ( IMS ) in adolescents the age of 15-24 years who got serious disease would as much as 92 a person with 4 the syphilis and 15 a person gonorrhea (GO).The purpose of this research to gain an understanding of the factors causing the behavior runs the risk of HIV/AIDS in adolescents.The place of research in four to senior high school in the working areas of the UPTD Puskesmas the hope of Raya Pekanbaru. A design study analytic cross-sectional with the total sample 314 teenagers appeared.An analyzer used the univariat, bivariat (chi square), and multivariate (regression double logistic).The analysis multivariate variable are associated with risky behavior hiv the sexes (OR: 28,838 CI: 95 % 9,084-91,549) and neighborhood (OR: 0,104 CI: 95 % 0,026-0,418). Conclusions sexes 28 times had a chance to behave risky HIV/AIDS and neighborhood 3 times risky HIV/AIDS. Advice recommended for the UPTD Puskesmas and schools turn back pkpr and activities youth to enhancing teen health.